DEVELOPMENT AND VALIDATION OF ANALYTICAL METHOD FOR DETERMINATION OF DONEPEZIL HYDROCHLORIDE IN PURE AND DOSAGE FORMS - SHIRWAIKAR, ARUN; DEVI, SARALA; RAJAGOPAL.P.L,; KIRON.S.S,; SREEJITH.K.R, (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To develop and validate a simple, precise and sensitive extractive spectrophotometric method for the assay of Donepezil HCl in pure and pharmaceutical preparations. Method: It is based on the formation of ion-pair complex between the drug and Bromo cresol purple in phthalate buffer solution. The formed complex was extracted with chloroform and measured at 410 nm. Results: Beer's law was obeyed in the range 2-14 μg/ ml with correlation coefficient (n = 6) ≥ 0.9999.The molar absorptivity, Sandell sensitivity, detection and quantification limits were also calculated. The composition of the ion pairs was found 1:1 by Job's method. Conclusion: This developed method was validated for accuracy and precision and has been applied successfully for the analysis of Donepezil in pure and in its dosage forms. KEY WORDS: Donepezil, chromophores, spectrophotometry, pharmaceuticals, Bromo cresol purple, ion pair